Horton: Online Query Execution Engine for Large Distributed Graphs (Demo Track) - Sarwat, Mohamed; Elnikety, Sameh; He, Yuxiong; Kliot, Gabriel (ICDE 2012: 28th IEEE International Conference on Data Engineering, 2012)
Large graphs are used in many applications, such as social networking. The management of these graphs poses new challenges because such graphs are too large to fit on a single server. Current distributed techniques such as map-reduce and Pregel are not well-suited for processing interactive adhoc queries against large graphs. In this paper we demonstrate Horton, a distributed interactive query execution engine for large graphs. Horton defines a query language that allows expressing regular language reachability queries and provides a query execution engine with a query optimizer that allows interactive execution of queries on large distributed graphs in parallel. In the demo, we show the functionality of Horton managing a large graph for a social networking application called Codebook, in which a graph models data on software components, developers, development artifacts (such as bug reports), and their interactions in large software projects.